Assessment of Sleep Quality among Medical Students During the Covid-19 Pandemic - Taha Naveed, Noor-E-Karim, Muhammad Rafeh, Ali Hassan Qayyum, Ashi Ahmed, Asma Hafeez, Aqsa Naheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the sleep quality among medical students, comparing their sleep cycles during physical and online studies along with other factors associated with sleep patterns. Study Design: Cross-sectional Questionnaire based survey Place and Duration of Study: Department of Community Medicine, HITEC Institute of Medical Sciences Taxila from 1st January 2020 to 31st March 2020 Methodology: One hundred and forty seven students were surveyed in a time period of 1 month. The questionnaire included PSQI Pittsburgh Sleep Quality Index and other clinically validated questions. Students with known sleeping disorders were excluded from this survey. Results: There were 81 (55.1%) females and 65 (44.2%) males with mean age 20±1.4 years. Out of these 94(63.9%) were classified as “Poor Sleepers” and only 53 (36.1%) were “Good Sleepers”. Poor sleep quality was associated with female gender (p<0.05), day-scholar residence status (p<0.054), excessive time required to sleep (p<0.00), excessive screen time usage (p<0.007), increased hours of study (p<0.089), experiencing trouble while driving, eating and socializing (p<0.002), lack of enthusiasm (p<0.000), unsatisfactory daily activities (p<0.000) and poor daytime alertness levels (p<0.360). 104 (70.7%) were aware of the effects of melatonin on sleep, only 51 (34.7%) admitted to have used coffee to stay awake at night. 98 (66.7%) subjects were pre-exam workers, 95 (64.6%) admitted not being able to wake up easily in the morning. Conclusion: The students and hostelites that used less screen time slept better. Excessive daytime tiredness was also a result of poor sleeping habits. Students who studied for longer periods of time and had difficulty waking up in the morning slept poorly. Poor sleepers also find it difficult to interact and are often unambitious about performing their daily menial tasks, as well as displeased with their daily activities. As a matter of fact, we deduce that sleep quality has unanticipated consequences for medical students' social and mental health. Keywords: Sleep Quality, Medical Student, Online Classes, PSQI, Excessive Daytime sleepiness, Epsworth sleepiness scale